1944
DOI: 10.1002/hlca.194402701197
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Erythrophleum‐Alkaloide. (7. Mitteilung). Über β‐Dialkylamino‐äthylester und β‐Dialkylamino‐äthylamide einiger Gallensäuren

Abstract: Die Erythrophleum-Alkaloide C a s s a i n , C a s s a i d i n und C o um i n g i n haben sich als p-Dimethylamino-iithylester von Diterpensauren erwiesen2). Da such andere Ester der ,t?-DiaIkylamino-Slthanole bemerkenswerte physiologische Eigenschaften besitzen3), so schien es von Interesse, zum Vergleich einige Ester solcher Basen mit den leicht zugiinglichen Gallensauren herzustellen und pharmakologisch zu prufen.Fiir die Herstellung der gesuchten ,L?-Dialkylamino-iithylester kamen vor allem folgende drei Xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1945
1945
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The p-bromoanilide derivative of desoxycholic acid, 3c~,12~-dihydroxycholanic acid (I), was prepared by methods outlined in the literature (Ruzicka, Plattner & Engle, 1944;Julian, Cole, Magnani & Meyer, 1945).…”
Section: Methodsmentioning
confidence: 99%
“…The p-bromoanilide derivative of desoxycholic acid, 3c~,12~-dihydroxycholanic acid (I), was prepared by methods outlined in the literature (Ruzicka, Plattner & Engle, 1944;Julian, Cole, Magnani & Meyer, 1945).…”
Section: Methodsmentioning
confidence: 99%
“…However, the duration of the positive inotropic effect produced by cassaine-type diterpenoid ester amines and amides was very short. Cronlund studied the metabolism of cassaidine (2) in Guinea pig and proposed that hydrolysis was responsible for the short duration [44].…”
Section: Digitalis-like Positive Inotropic Action On the Heartmentioning
confidence: 99%
“…It was found that ester amines and amides are readily distinguished by the intense base peak in their mass spectra. Those of dimethylaminoethanol esters, such as cassaine (1), cassaidine(2), and cassamidine(10), have the most intense peaks arising from the N-containing side chain. The extremely intense ions at m/z 71 and 58 are attributed, respectively, to the fragmentCH 2 =CH-N +• (CH 3 ) 2 ,formed by McLafferty rearrangement, and to the fragment CH 2 =N + (CH 3 ) 2 , formed by fission of the C-C bond next to the Natom.…”
mentioning
confidence: 99%
“…The potent positive inotropic cardiac activity present in both the steroidal cardiac glycosides and the erythrophleum alkaloids led two groups of workers to prepare steroidal analogues of the latter, in which bile acids were used to replace the diterpenoid acids as supporting moieties (Ruzicka, Plattner and Engel, 1944;Uhle, Mitman and Krayer, 1956), but the new compounds were virtually inactive. It will be interesting to see whether steroidal esters of pyrrole -a-carboxylic acid will be prepared as analogues of the diterpenoid alkaloid ryanodine (Valenta and others, 1962) which exhibits such a remarkable pharmacological action on muscle (Hillyard and Procita, 1959 and refs.…”
Section: XXImentioning
confidence: 99%